2004
DOI: 10.1210/jc.2003-030550
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Routine Measurement of Serum Calcitonin on the Diagnosis and Outcome of Medullary Thyroid Cancer: Experience in 10,864 Patients with Nodular Thyroid Disorders

Abstract: The survival rate of patients with medullary thyroid carcinoma (MTC) is significantly better in patients diagnosed and treated when the tumor is limited to the thyroid. In a pioneer study carried out in 1991, we demonstrated that routine measurement of serum calcitonin (CT) in nodular thyroid disease allowed the preoperative diagnosis of unsuspected sporadic MTC with better accuracy than routine fine needle aspiration cytology (FNAC). This finding has been confirmed in subsequent studies. In the present study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
271
1
41

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 466 publications
(335 citation statements)
references
References 36 publications
(30 reference statements)
20
271
1
41
Order By: Relevance
“…Routine measurement of serum thyroglobulin for initial evaluation of thyroid nodules is not recommended-Recommendation F Serum calcitonin measurement. The utility of serum calcitonin has been evaluated in a series of prospective, nonrandomized studies (24)(25)(26). The data suggest that the use of routine serum calcitonin for screening may detect C-cell hyperplasia and medullary thyroid cancer at an earlier stage FIG.…”
Section: Other Laboratory Testingmentioning
confidence: 99%
“…Routine measurement of serum thyroglobulin for initial evaluation of thyroid nodules is not recommended-Recommendation F Serum calcitonin measurement. The utility of serum calcitonin has been evaluated in a series of prospective, nonrandomized studies (24)(25)(26). The data suggest that the use of routine serum calcitonin for screening may detect C-cell hyperplasia and medullary thyroid cancer at an earlier stage FIG.…”
Section: Other Laboratory Testingmentioning
confidence: 99%
“…More significant is that non-specific cytological features may wrongly suggest tumors other than MTC. These false negative diagnoses result in the failure to cytologically diagnose MTC, and lower cytological sensitivity for MTC (45,(47)(48)(49)(50)(51)(52)(53)(54)). An abstract reporting 14 samples (from 13 patients) that positively expressed the MTC gene expression signature in the Afirma GEC rare neoplasm cassettes found that all 14 were confirmed as MTC on histopathology (55).…”
Section: Rare Neoplasmsmentioning
confidence: 99%
“…MTC arises from the neural crestderived parafollicular C cells (4), presents in the familial form with a genetic mutation in 25% of the cases (1,5), and is the most aggressive of differentiated thyroid carcinomas, with a survival rate at 10 years approaching 40-50% and depending on the tumor stage at diagnosis (3,27). In the literature, a convincing body of evidence exists showing that when the neoplasm is confined within the thyroid and thyroidectomy with dissection of the central lymph node compartment is performed, the chance of definitive cure is high (3,10,28). Therefore, early detection of MTC is crucial to perform the best surgical approach before extrathyroidal dissemination and to save the patient's life.…”
Section: The Thyroid Isthmus and The Parafollicular C Cellsmentioning
confidence: 99%
“…Actually, two diagnostic tools are available for the evaluation of patients with NTD, including those with MTC: FNAC and measurement of human C t concentrations. Previous European studies recruiting large series of patients with NTD (6)(7)(8)(9)(10)(11)(12) demonstrated that it is possible to diagnose MTC earlier with C t screening than FNAC, particularly in patients with nodules smaller than 10 mm (microMTCs). Hence, the ETA has recommended C t screening in all subjects with NTD (13).…”
Section: The Thyroid Isthmus and The Parafollicular C Cellsmentioning
confidence: 99%
See 1 more Smart Citation